The copy number variation landscape of congenital anomalies of the kidney and urinary tract - Verbitsky, Miguel; Lozanovski, Vladimir J. (Nature genetics, 2019)
Genome-wide analysis of copy number variants in 2,824 cases across the phenotypic spectrum of CAKUT sheds light on the genomic architecture of disease and identifies TBX6 as a driver for CAKUT subphenotypes in the 16p11.2 microdeletion syndrome.
Published online: 21 December 2018
Gesehen am 10.07.2019